Skate Life Re-Imagining White Masculinity - Yochim, Emily Chivers (University of Michigan Press, 2010)
"Intellectually deft and lively to read, Skate Life is an important addition to the literature on youth cultures, contemporary masculinity, and the role of media in identity formation." ---Janice A. Radway, Northwestern University, author of Reading the Romance: Women, Patriarchy, and Popular Literature "With her elegant research design and sophisticated array of anthropological and media studies approaches, Emily Chivers Yochim has produced one of the best books about race, gender, and class that I have read in the last ten years. In a moment where celebratory studies of youth, youth subcultures, and their relationship to media abound, this book stands as a brilliantly argued analysis of the limitations of youth subcultures and their ambiguous relationship to mainstream commercial culture." ---Ellen Seiter, University of Southern California "Yochim has made a valuable contribution to media and cultural studies as well as youth and American studies by conducting this research and by coining the phrase 'corresponding cultures,' which conceptualizes the complex and dynamic processes skateboarders employ to negotiate their identities as part of both mainstream and counter-cultures." ---JoEllen Fisherkeller, New York University Skate Life examines how young male skateboarders use skate culture media in the production of their identities. Emily Chivers Yochim offers a comprehensive ethnographic analysis of an Ann Arbor, Michigan, skateboarding community, situating it within a larger historical examination of skateboarding's portrayal in mainstream media and a critique of mainstream, niche, and locally produced media texts (such as, for example, Jackass, Viva La Bam, and Dogtown and Z-Boys). The book uses these elements to argue that adolescent boys can both critique dominant norms of masculinity and maintain the power that white heterosexual masculinity offers. Additionally, Yochim uses these analyses to introduce the notion of "corresponding cultures," conceptualizing the ways in which media audiences both argue with and incorporate mediated images into their own ideas about identity. In a strong combination of anthropological and media studies approaches, Skate Life asks important questions of the literature on youth and provides new ways of assessing how young people create their identities. Emily Chivers Yochim is Assistant Professor in the Department of Communication Arts, Allegheny College. Cover design by Brian V. Smith